PERMINTAAN DALAM BAHASA MINANGKABAU - Ike Revita; I Dewa Putu Wijana; Soepomo Poedjosoedarmo (Humaniora, 2007)
This paper aims at describing the ways how Minangkabau people request. These ways are prospected from the syntactical form and the types of the request. The factors influencing the choice of these ways are also observed. The data are taken from Minangkabau utterances used in Padang. The results of the research indicate that Minangkabau people use declarative, interrogative, imperative, and exclamative sentences to make requests. Further, the result shows that the requests can be expressed in direct, indirect, literal, non literal, direct literal, indirect literal, direct non literal, indirect non literal types depending on the participants, the situation, the topics, and the norms.